Integrity as a Value in Organisations - Czajkowska-Białkowska, Maria (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: To examine the important problem of honesty in organisational behaviour, and to answer questions concerning the respondents’ opinions on dishonest behaviours of two groups of organisational participants: managers / directors and employees / subordinates.Research Design & Methods: The research was conducted using questionnaire adapted for the research.Findings: The results show the difference between the behaviours of managers/directors and those of employees/subordinates. The research indicates that particular dishonest behaviours are more frequent among managers/directors than among employees/subordinates, although the findings are not completely conclusive.Implications / Recommendations: The conclusions provide a basis for further research involving in-depth studies on the motives for the occurrence of such behaviours by members of both groups in an organisation.Contribution: The article concerns the value of honesty in organisations in the context of the exercise of power. Drawing attention to the problem, which affects all members of an organisation to a different extent, may help to shape ethical attitudes of future managers and, in consequence, to manage the organisation better.